The Impact of Interpersonal Communication on Thesis Completion Motivation among KPI Students - Armadila, Armadila; Wahyunisa, Wahyunisa; Andriani, Yuli; Ayu Saadah, Neng; Dafrizal, Dafrizal (Suluah Pasaman, 2026)
This study examines the role of interpersonal communication in enhancing thesis completion motivation among KPI 2022 batch students at STAI YDI Lubuk Sikaping, where low motivation often leads to procrastination and delayed graduation. Grounded in interpersonal communication, role, and motivation theories, this descriptive qualitative study collected data through in-depth interviews, observation, and document analysis using purposive sampling. Findings reveal that harmonious supervisor-student communication including clear guidance, constructive criticism, and emotional support significantly strengthens students' self-confidence and consistency. Positive reinforcement, intrinsic motivation, and support from family and peers form an effective synergy, while negative reinforcement such as criticism and deadlines functions as a productive stimulus rather than an obstacle. This study contributes empirical evidence from an Islamichigher education context in West Sumatra, demonstrating that supervisor-student interpersonal communication serves as a multidimensional motivational mechanism bridging relational, emotional, and academic dimensions of thesis supervision